2009
DOI: 10.1063/1.3147868
|View full text |Cite
|
Sign up to set email alerts
|

Nanograin crystalline transformation enhanced UV transparency of annealing refined indium tin oxide film

Abstract: Articles you may be interested in UV irradiation effect on sol-gel indium tin oxide nanopatterns replicated by room-temperature nanoimprint

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…4. The sheet resistances of the ITO thin films are strongly related to the amount of oxygen vacancies and microstructure [15]. The oxygen vacancies create maximum two free electrons per vacancy to the donor level through ionization, leading to an increase in conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…4. The sheet resistances of the ITO thin films are strongly related to the amount of oxygen vacancies and microstructure [15]. The oxygen vacancies create maximum two free electrons per vacancy to the donor level through ionization, leading to an increase in conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…These results confirm that the annealing temperature below 500 C does not seriously affect the optical transmittance even though the crystallization of AYZO films is improved by increasing the annealing temperature. Conversely, the 325-nm and 405-nm transmittance of ITO films can be improved by 4 and 1.5 times, respectively, within the annealing temperature range of 400 C-500 C. The highest 325-nm transmittance of the ITO films was observed at the annealing temperature of 475 C. However, the 325-nm transmittance degrades to 28.5% when increasing the annealing temperature above 500 C. The crystallization of ITO films after high-temperature annealing is known to be detrimental to the UV transmittance [10]. Apparently, the comparisons have also shown that the AYZO exhibits a better transmittance that the ITO at wavelengths longer than 405 nm.…”
Section: Resultsmentioning
confidence: 83%
“…Nevertheless, the resistivity of ITO films increases to 7 10 cm by further increasing the annealing to 475 C or higher. In view of previous works, the resistivity of the AZO film with Al content of 7 at.% deposited by using the RF magnetron sputtering can be controlled below 4.7 10 cm, which has the transmittance up to 90% at visible wavelength regime [37]. In comparison with the AZO films, the AYZO film with lower donor content (Al: 0.7 wt.% and Yb: 0.5 wt.%) also achieves a similar resistivity of 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations